POLA ASUH ORANG TUA DALAM MENDIDIK ANAK PADA KELUARGA PETANI DI DESA GONIS TEKAM - Wulandary, Aznie Saputri; Buwono, Sri; Ulfah, Maria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to determine parenting style and the form of parenting applied by parents in educating children to farmer families in Gonis Tekam Village, Sekadau Hilir Subdistrict, Sekadau District. This study uses a qualitative approach with the phenomenal method. Data analysis techniques in this study are data reduction, data display, and verification. The results showed that parenting was considered poor, parents gave less attention, seen from the lack of parents in reminding the time to children, lack of advice to children and parents did not say soft and polite to children, parental care for children less visible when parents never give gifts, lack of providing for children's needs and not fully providing support to children, especially in children's hobbies, supervision of parents is very loose on children such as not supervising children's activities, not looking for information about children and not reprimanding children do it. The form of parenting applied by parents in educating children is permissive parenting in which parents tend to give full freedom to children, with permissive parenting children tend to behave negatively and deviate from community norms. Keywords: Educating, Farmer Family, Parenting